Validación de un protocolo fotográfico digital para análisis macroscópico de la anatomía y colorimetría en madera de especies arbóreas de Costa Rica - Valverde, Juan Carlos; Arias, Dagoberto; Figueroa, Geovanni; Mata, Erick; Zamora, Nelson (Ingeniería, 2022)
Context: The process of digitizing wood samples for identification and study has become relevant over the past decade, so it is necessary to consider the photographic aspects that generate representation of the images with respect to the physical sample. Method: Ten woodable species were used with no less than 10 sampled trees, from each individual five 10 mm edge wooden cubes were ex-brought and photographed with a stereoscope with a 20X under four luminosity protocols. In the process, the variation in color (under the coordinates L*, a* and b*), color differential (E*) and chroma (C*), in addition to the density and diameter of vessels, was evaluated. Results: The results showed that the brightness of 50% showed the greatest similarity to the colorimetry of the wood, obtaining values of E* less than 6 in all species and values of C* within the optimal range of 5 to 7. With respect to the anatomical part, the same behavior was given with the ten species, finding that the luminosity treatments at 25 and 50 % showed no significative differences, while the luminosities of 75 and 100% tended to underestimate the value. Conclusions: The treatment luminosity at 25% is ineffective by the darkening of the surface, while exposures to 75 and 100% tended to clarify the surface area and underestimate anatomical characteristics.